2020
DOI: 10.1002/sim.8475
|View full text |Cite
|
Sign up to set email alerts
|

A robust Bayesian mixed effects approach for zero inflated and highly skewed longitudinal count data emanating from the zero inflated discrete Weibull distribution

Abstract: This article proposes a Bayesian mixed effects zero inflated discrete Weibull (ZIDW) regression model for zero inflated and highly skewed longitudinal count data, as an alternative to mixed effects regression models that are based on the negative binomial, zero inflated negative binomial, and conventional discrete Weibull (DW) distributions. The mixed effects ZIDW regression model is an extension of a recently introduced model based on the DW distribution and uses the log‐link function to specify the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The conventional discrete Weibull distribution's key properties, including its dispersion, zero‐inflation, and heavy‐tail indices, can be found in Luyts et al 8 Burger et al 11 present an extension of the DW distribution by adding a zero‐inflation parameter; hence, the so‐called ZIDW distribution. The remainder of this section provides a summary of the ZIDW distribution.…”
Section: Conventional Zidw Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…The conventional discrete Weibull distribution's key properties, including its dispersion, zero‐inflation, and heavy‐tail indices, can be found in Luyts et al 8 Burger et al 11 present an extension of the DW distribution by adding a zero‐inflation parameter; hence, the so‐called ZIDW distribution. The remainder of this section provides a summary of the ZIDW distribution.…”
Section: Conventional Zidw Distributionmentioning
confidence: 99%
“…The PMF of the ZIDW distribution, using the parameterization of Burger et al 11 for a given count yi, is written as: fyi|μ,ϕ,π=πIyi=0+1πexplog2yiμϕexplog2yi+1μϕ Here, ϕ and π are, respectively, the shape parameter and zero‐inflation probability, and μ is the median of the conventional discrete Weibull distribution. The median of the yi under the ZIDW distribution is given by: Myi=λ=log0.51πlog0.51ϕμ Recently, Burger et al 11 suggested the use of the log‐link function to model μ. Taking an approach similar to that of Preisser et al, 13 λ's modeling is suggeste...…”
Section: Marginal Zero‐inflated Count Distributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their approach was used to identify potential disparities in outpatient psychiatric service use among white, black, and Latino homeless adults receiving case management. Burger, Schall, Ferreira, and Chen (2020) developed a Bayesian mixed effects approach for highly skewed longitudinal count data that are ZI. In particular, they developed this approach assuming a ZIDW regression model and a matrix generalized half‐ t prior distribution for the covariance matrix of the random effects, instead of the commonly used Wishart prior.…”
Section: Zero Inflation In Correlated Count Settingsmentioning
confidence: 99%